Instrumenation and sensors for the food indudtry - Kress-Rogers, E. (Woodhead Publishing, 2011)
This book is of central importance to the vast food industry, with particular emphasis on very high sanitary and hygienic operating standards. This comprehensive reference covers the wide range of instruments used in the industry with contributions from an international panel of specialists.